Stability Analysis of Lowwall Slopes in Limestone Mining at PT Semen Baturaja (Persero) Tbk, Ogan Komering Ulu Regency, South Sumatra Province - Sutejo, Dwiki; Safaruddin; Haryoto, Y. (ReTII, 2023)
PT Semen Baturaja (Persero) Tbk is a mining company located in West Baturaja District, Ogan Komering Ulu Regency, South Sumatra Province which is engaged in the mining and processing of Limestone and Clay. Slope stability is one of the most important aspects in the world of mining because slopes are directly related to the safety of workers, equipment and the mining process itself. This research uses the limit equilibrium method of the bishop model with the final result being the value of the factor of safety. The parameters used in this method are the cohesion value, the internal shear angle value and the rock density value. This analysis was carried out on the lowwall mining slope of PT Semen Baturaja (Persero) Tbk by conducting try and error of the mining slope geometry, so that the overall slope geometry is safe with dynamic safety factor > 1.25